Verso la sostenibilità e …oltre! Utilizzo del Game-based learning per la promozione della chimica sostenibile nelle scuole secondarie - Testa, Maria Luisa; Russo, Marco; Aliotta, Chiara; Zanelli, Alberto; Torreggiani, Armida; Deganello, Francesca (Chimica nella Scuola, 2025)
Green and sustainable chemistry is an important piece of the skills puzzle needed to foster a cultural shift in society toward sustainability, circular economy and decarbonization. We propose a learning path on Chemistry and Sustainability which exploits the Game-Based Learning and is structured in two steps. The first one is to introduce and contextualize the concepts with the games “Sustainable Crosswords”, “New materials from Waste,” and “Reduce, Recycle, Reuse,” and the second one to go into details and consolidate with the game “Toward Sustainability... and Beyond”. The training objectives include both cognitive processes and learning content.